2011
DOI: 10.1002/jso.21815
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nodal status and tumor burden in sentinel lymph nodes on the clinical outcomes of cancer patients

Abstract: The validation of sentinel lymph node (SLN) concept in melanoma and breast cancer has established a new paradigm in cancer metastasis that, in general, cancer cells spread in a orderly fashion from the primary site to the SLNs in the regional nodal basin and then to the distant sites. In this review article, we examine the development of SLN concept in penile carcinoma, melanoma and breast carcinoma and its application to other solid cancers with emphasis of the relationship between micrometastasis in SLNs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 159 publications
1
35
0
Order By: Relevance
“…3). However, since LNs are one main source of tumor spread and metastases (summarized in [79]), a case-by-case decision regarding the length of time that a diseased LN should remain in the patient's body would have to be made by the clinical team. Very recently, Burnette and colleagues have demonstrated that RT drastically enhances the number and cross-priming capacity of tumor-infiltrating CD11b + /Ly-6C + /MHC class II + DCs in a type I interferon-dependent manner [80].…”
Section: Radiotherapy and Immune Activationmentioning
confidence: 99%
“…3). However, since LNs are one main source of tumor spread and metastases (summarized in [79]), a case-by-case decision regarding the length of time that a diseased LN should remain in the patient's body would have to be made by the clinical team. Very recently, Burnette and colleagues have demonstrated that RT drastically enhances the number and cross-priming capacity of tumor-infiltrating CD11b + /Ly-6C + /MHC class II + DCs in a type I interferon-dependent manner [80].…”
Section: Radiotherapy and Immune Activationmentioning
confidence: 99%
“…These may eclipse both PD1 and CTLA-4, and our decade old therapy IL-2, but it's the tumor infiltration that may be a biomarker of very great relevance to all of these outcomes. This whole conference on nodal disease began with Stanley Leong's clairvoyant realization that the node is the turnstile through which this tumor travels in the majority of patients [138]. We have ignored the lymph node—(not the surgeons here, but many outside of the surgical community) have ignored the node despite performing sentinel node biopsy upon hundreds of patients each year.…”
Section: Discussant Summary and Commentmentioning
confidence: 99%
“…1 In addition to tumor size, lymph node status (positive/negative lymph node metastasis) is regarded as the strongest prognostic factor for patient's cancer-specific survival. 2,3 It is widely used for guiding therapeutic decisions and currently justifies a systematic lymphadenectomy in early cervical cancer.…”
mentioning
confidence: 99%